Upaya Meningkatkan Disiplin Guru Dalam Kehadiran Mengajar di Kelas Melalui Penerapan Buku Pratinjau di SMKN 2 Gedangsari Kabupaten Gunungkidul - Supiningsih Supiningsih (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to reduce empty hours at school, reduce the number of teachers who are coming late to school, reduce the number of teachers who coming late for class. The reseacher subjects were 56 teachers at Gedangsari Vocational School. The object of the study was the monitoring of teachers coming to school and entering the classroom by applying the â€œBuku Pratinjauâ€. The method of this research is School Action Research using two cycles on an ongoing basis. Data collection techniques using observation and documentation. The results of the study are the application of theâ€Buku Pratinjauâ€ can improve the performance of teachers in SMKN 2 Gedangsari indicated by an increase in teachers coming to school from the initial condition of 33 remaining 6 teachers. As well as an increase in teachers entering the classroom from the initial condition of 24 remaining 6 teachers are late.